MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS X MA AL MA’ARIF DENGAN MENERAPKAN PEMBELAJARAN GENERATIF TAHUN PELAJARAN 2017/2018 - Muzaki, Ahmad; Apriani, Yuyun; Juliangkary, Eliska (Media Pendidikan Matematika, 2018)
This study aims to improve the learning activeness of students in grade X of MA Al-Maâ€™Arif Academic Year 2017/2018 by applying generative learning. The type of research used was classroom action research (CAR). This research was conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. There were 2 meetings for each cycle. The average value of learning activeness data of student in the first cycle were 35.8 and 40.6 (first and second meetings), with categories of dislike and hesitation. And in the second cycle were 53.2 and 63.2 with categories of hesitation and likes. Thus it could be concluded that by applying generative learning can improve student learning activeness.Â